Cucurbitane Triterpenoids from the Fruit Pulp of Momordica charantia and Their Cytotoxic Activity. Issue 5 (28th January 2013) - Liao, Yun‐Wen; Chen, Chiy‐Rong; Chuu, Jiunn‐Jye; Huang, Hui‐Chi; Hsu, Jue‐Liang; Huang, Tzou‐Chi; Kuoe, Yueh‐Hsiung; Chang, Chi‐I
Abstract Two new cucurbitane‐type triterpenes, 25‐methoxycucurbita‐5, 23(E)‐diene‐3β, 19‐diol (1) and 7β‐ethoxy‐3β‐hydroxy‐25‐methoxycucurbita‐5, 23(E)‐dien‐19‐al (2), together with three known cucurbitane‐type triterpenes, 3β, 7β, 25‐trihydroxycucurbita‐5, 23(E)‐dien‐19‐al (3), (23E)‐3β‐hydroxy‐7β, 25‐dimethoxycucurbita‐5, 23‐dien‐19‐al (4), and 3β‐hydroxy‐25‐methoxycucurbita‐6, 23(E)‐dien‐19, 5β‐olide (5), were isolated from the fruit pulp of Momordica charantia. The structures of two new compounds were elucidated on the basis of 1D and 2D NMR, MS, IR, optical rotation. Among these isolates, compounds 1, 2, and 5 showed slight cytotoxic activity against the SK‐Hep 1 cell line with IC50 values of 33.1, 24.3, and 38.7 μM, respectively.